Comparative Approach to Flexural Behavior of Reinforced Beams with GFRP, CFRP, and Steel Bars - Naser Kabashi; Besart Avdyli; Enes Krasniqi; Arbër Këpuska (Salehan Institute of Higher Education, 2020)
The replacement of conventional steel bars with GFRP or CFRP is one of the main topics discussed in this paper, including the main parameters and properties of the materials. The design procedures should account for the properties and will focus on the tensile strength and modulus of elasticity. It will also consider corrosion under environmentally aggressive conditions. This paper presents an experiment on the flexural behavior of concrete beams reinforced with GFRP and CFRP bars and compares these results with theoretical analysis based on different standards such as ACI, Eurocode, and CSA. Twelve reinforced concrete beams will be tested using four-point loading. The geometrical parameters of the tested beams are 130×220×2200 mm, reinforced with different diameters for GFRP and CFRP. The reinforcement ratio and strength of concrete influence the behavior of GFRP, CFRP, and RC beams and contribute to reduce the deflection and crack width. Based on this research, the closest approximation of the experimental results is observed with ACI standards. At this stage, these bars can be used in structures without strict requirements for exceeding the Serviceability Limit State. The non-integration of tension stiffening and regression performance of cracking moment in prediction expressions imposed the differences from experimental results.